If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4q = 8q Solving 4q = 8q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-8q' to each side of the equation. 4q + -8q = 8q + -8q Combine like terms: 4q + -8q = -4q -4q = 8q + -8q Combine like terms: 8q + -8q = 0 -4q = 0 Divide each side by '-4'. q = 0 Simplifying q = 0
| 8/9=30+a/45 | | x+3+3x=4(x-1) | | h=0.01x^2-x+27 | | 6(n-5)+8= | | 6n+4=-4n-16 | | 15x+15=90 | | 2x+4=52 | | 1/9=a/a+24 | | 81x^2+162x+17=0 | | (3x-17)=(2x+8) | | 6-4= | | 180=90+(8x+2)+(9x+3) | | (3x+39)=(6x-12) | | 2x+3y+5=0 | | (8-1)/4=2/3 | | -7x^2=21 | | 26/15=104/70-w | | 2x-12=x+12 | | 2x^2+5y^2-22=0 | | x^2-2x-2=-2x^2+9x+2 | | 6(18)-57=2(18)+15 | | 4x-2=154 | | 10-4(6)+2= | | 30x+12-10=6 | | -3(x+2)=3(x+2) | | 6-5(2-4x)=14 | | -15+10+(-6)+4= | | 8x-(x-5)+(3x+2)=x-14 | | (5x-24)=90 | | (3x-30)=90 | | 12-10= | | h=-16t^2+t |